2018
DOI: 10.33225/pec/18.76.587
|View full text |Cite
|
Sign up to set email alerts
|

Leadership, School Improvement and Effectiveness: The Experiences of the Schools Community in Ethiopia

Abstract: This was a qualitative research, which explored how the school community experienced the outcomes of leadership on the effectiveness of the school improvement program (SIP) on Sidama Zone schools, Ethiopia. Four schools were purposively selected. Data were collected using interviews, focus group discussions, observation and documents, which included school plans, reports, minutes of meetings, memos, letters and the students' examination results were analyzed as they reflected issues related to the outc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…This can also be associated with the claims of Ray (2018) that managers who take on supervisory roles often serve as mentors. Likewise, Edamo and Netshitangani (2018) whose findings indicate that in schools where there is a strong collaboration of the necessary. Similar to the other categories, constant communication, awareness of the rules to observe, and the observance of context, were helpful.…”
Section: How District and Division Supervisors Addressed The Challeng...mentioning
confidence: 98%
“…This can also be associated with the claims of Ray (2018) that managers who take on supervisory roles often serve as mentors. Likewise, Edamo and Netshitangani (2018) whose findings indicate that in schools where there is a strong collaboration of the necessary. Similar to the other categories, constant communication, awareness of the rules to observe, and the observance of context, were helpful.…”
Section: How District and Division Supervisors Addressed The Challeng...mentioning
confidence: 98%
“…| 457 external evaluation (Edamo & Netshitangani, 2018); the whole cycle requires 3 years of strategic planning and yearly action plans based on the results of self-assessment (Ebuy, 2010) (see Figure 1). Thus, in one way or another, it is evident that the absolute implementation of the SIP bank on principal leadership behavior should be apt for creating a favorable atmosphere for school teachers, staff members, and, most importantly, for SIP committee members that promote a coherent SIP process.…”
Section: The Ethiopian Contextmentioning
confidence: 99%
“…Ethiopia has exhibited a radical 500% improvement in basic or primary education enrollment (MoFED, 2012 Gurmu, 2020; Mitchell, 2015), despite the poor school infrastructure, instructional practice, school leadership, and underdeveloped education system (Yohannes & Wasonga, 2021). Hence, school principals in primary and secondary schools in Ethiopia officially obtained autonomy (decentralized system) in administering and decision‐making regarding financial, human, and physical resources through a feasible national package known as the General Education Quality Improvement Package (GEQIP) in 2007, which consisted of six sets of programs, namely, the School Improvement Program (SIP), Information Communication Technology (ICT), Civic and Ethical Education Program, Teacher Development Program (TDP), Curriculum Improvement Program, and School Management and School Leadership (Abdi, 2016; Ebuy, 2010; Edamo & Netshitangani, 2018; Gedifew, 2020; Gurmu, 2018; MOE, 2007). Above all others, the SIP entitles principals to acquire autonomous authority to lead SIP implementation by recruiting and inducting teachers, managing budgets, and participating in decision‐making regarding curriculum development and improvement (Mitchell, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…This finding was also supported among the least developed countries. Edamo (2018), conducting a quantitative study focussing on the level of parental involvement and its implications for student's learning in secondary schools in Ethiopia, found that there was very low parental involvement which was limited to sending children to school. Sapungan and Sapungan (2014), who have been school administrators for over a decade in Bahrain and the Philippines, underscore the notion that over the years parental involvement has been on a steady decline much to the frustration of principals and teachers whose efforts to boost parental involvement are proving futile.…”
Section: Evidence Of Problem From International Literaturementioning
confidence: 99%
“…In the province of Saskatchewan in Canada, there was an amendment to the provincial/territorial Education/School Acts to mandate the implementation of a School Community Council in every public school to encourage the active involvement of parents and community (Preston, 2011). Such policies also exist on the continent of Africa in countries such as South Africa, Kenya, Uganda, and Ethiopia (Edamo, 2018;Magwa & Mugari 2017).…”
Section: Evidence Of Problem From International Literaturementioning
confidence: 99%